The rights of illegitimate children in Malaysia from the perspectives of civil and Islamic laws / Muhammad Asnawi Mohamad Rais … [et al.] - Mohamad Rais, Muhammad Asnawi; Mohd Sairy, Noor Asyura; Khairul Zaman, Noorhalissa; Abd. Rahim, Siti Maisarah (2009)
This research aims to look at the rights of illegitimate children in Malaysia from the perspective of both civil and Islamic laws. Illegitimate children are children who were conceived during unlawful unions and are generally deprived of their rights to live as ordinary children. Hence, this research focuses on establishing a Legitimacy Act for illegitimate children. At present, the welfare of the illegitimate children is under the concern of the National Registration Department (JPN) and the Department of Social Welfare Malaysia (JKM) concerning the status of illegitimate children being legalized by way of adoption. From the research it is found out that the rights of the illegitimate children are guaranteed by the Welfare Department by focusing on the interest and benefits of the children. However, there is no specific department to collect statistics and to update on the number of illegitimate children in Malaysia. This makes it difficult for the Welfare Department to locate and protect these children. For that reason, we would like to promote laws which govern both Muslim and non Muslim illegitimate children where the main focal point is to ensure they get equal rights to legitimate children. Therefore, in conclusion, the rights of illegitimate children should be protected by way of a single law governing protection for them. The measure is to ensure that they have the opportunity to live and lead a normal life without having to bear humiliation and disgrace by the society.